DEVELOPING A SIMPLIFIED CLINICAL FRAILTY SCALE FOR ELDERLY PATIENTS - Nguyen Van , Tri; Nguyen Tran To , Tran; Le Thi Hong , Hoa; Tran Minh , Giao (Tạp chí Y Dược Thực hành 175, 2024)
Background: The Clinical Frailty Scale (CFS) assesses the degree of frailty based on simple clinical observations, comorbidities, functional status, and activity level in elderly patients. However, non-geriatric physicians often face challenges using this scale to evaluate frailty, so simplifying the Clinical Frailty Scale is a necessary problem for implementation and research. Objective: To develop a simplified clinical frailty scale based on the Clinical Frailty Scale. Research Subjects and Methods: Twenty medical doctors, including geriatric specialists and other specialists, were surveyed regarding the comprehensibility and applicability of the simplified Clinical Frailty Scale (CFS). Results: Most medical doctors (90%) agreed with the simplified Clinical Frailty Scale and will use the scale to assess frailty in elderly patients (90%), with no suggestions for editing terminology Conclusion: The simplified Clinical Frailty Scale used simpler terminology and more concise, and memorable terms than the original Clinical Frailty Scale, therefore, it was highly applicable and allowed non-geriatric physicians to assess frailty easily in elderly patients.